Chaos based IQ encryption for PAPR reduction and security enhancement in OFDMA PON system - Zhang, Wei (2018)
This paper proposed a quadrature amplitude modulation (QAM) encryption technique in orthogonal frequency-division multiple access-based passive optical network (OFDMA-PON) systems. This scheme combines chaos based IQ-encryption with the SLM technique. The system can benefit of simultaneous low PAPR and high physical layer security. For IQ encrypting, the real (I) and imaginary (Q) parts of the QAM symbols are separately coded with key sequences, which are generated by a logistic map. A bank of OFDM symbol candidates is obtained by repeating this process. Then the candidate with the lowest PAPR is transmitted to the ONU sides. The iteration parameters of the mapping formula are set as the security keys, which are securely transmitted between OLT and ONUs. The research has utilized this method to successfully transmit 10 Gb/s 16QAM OFDM signal along 30 km standard single mode fiber (SSMF).